2020
DOI: 10.3390/nu12103209
|View full text |Cite
|
Sign up to set email alerts
|

The Health Benefits of Dietary Fibre

Abstract: Background: Dietary fibre consists of non-digestible forms of carbohydrate, usually as polysaccharides that originate from plant-based foods. Over recent decades, our diet within Westernised societies has changed radically from that of our hominid ancestors, with implications for our co-evolved gut microbiota. This includes increased ingestion of ultra-processed foods that are typically impoverished of dietary fibre, and associated reduction in the intake of fibre-replete plant-based foods. Over recent decades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
369
3
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 497 publications
(398 citation statements)
references
References 86 publications
7
369
3
19
Order By: Relevance
“…However, despite these compelling data that support the beneficial effects of dietary fibre intake on insulin sensitivity, there were relatively few controlled studies (with a notable exception [ 93 ] that reported on the longer-term (>12 months) metabolic effects of dietary fibre intake [ 96 ]. This should be a focus for future research, to provide further evidence to promote the widespread adoption of a high-fibre diet within the populace [ 97 ].…”
Section: Reversibility Of Ir With Lifestyle Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, despite these compelling data that support the beneficial effects of dietary fibre intake on insulin sensitivity, there were relatively few controlled studies (with a notable exception [ 93 ] that reported on the longer-term (>12 months) metabolic effects of dietary fibre intake [ 96 ]. This should be a focus for future research, to provide further evidence to promote the widespread adoption of a high-fibre diet within the populace [ 97 ].…”
Section: Reversibility Of Ir With Lifestyle Interventionsmentioning
confidence: 99%
“…Within the existing literature, current dogma implicates effects of dietary fibre on SCFAs. More relevant to soluble, fermentable fibre, at least some of the metabolic benefits probably do occur via effects on the gut microbiome, with subsequent release of SCFAs [ 97 ]. Through effects both locally within the ileum and following absorption across the ileal wall into the bloodstream, SCFAs may in turn influence the release of various gut hormones [ 98 , 99 , 100 , 101 , 102 , 103 ], adipokines [ 104 ], bile acids [ 105 ] and amino acid metabolic signatures [ 106 ], each of which may contribute towards overall insulin sensitivity.…”
Section: Reversibility Of Ir With Lifestyle Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary fiber possesses an ability to prevent or relieve constipation and foods containing fiber can provide other health benefits as well, such as helping to maintain a healthy weight and lowering your risk of diabetes, heart disease and some types of cancer [ 111 ]. Few Artemisia species have been studied for the content of dietary fiber ( Table 2 ).…”
Section: Nutritional Value Of Artemisia Speciesmentioning
confidence: 99%